2012
DOI: 10.1080/09588221.2011.636053
|View full text |Cite
|
Sign up to set email alerts
|

Learners' perceptions of the pedagogical relations in a flexible language learning system

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 12 publications
0
4
0
1
Order By: Relevance
“…El programa posibilita el desarrollo de las actividades de aprendizaje virtuales en el tiempo de preferencia de los estudiantes y se acomoda al ritmo de estudio de cada individuo. Hallazgos similares se encuentran en un estudio con población universitaria en donde los estudiantes informaron altos niveles de satisfacción respecto a un sistema flexible de aprendizaje de lenguas, considerando que podían trabajar a su propio ritmo y que tenían la oportunidad de realizar los trabajos de forma autónoma (Chateau y Zumbihl, 2012).…”
Section: Flexibilidad Vs Barreras De Tiempo En El Aprendizaje De Inglésunclassified
“…El programa posibilita el desarrollo de las actividades de aprendizaje virtuales en el tiempo de preferencia de los estudiantes y se acomoda al ritmo de estudio de cada individuo. Hallazgos similares se encuentran en un estudio con población universitaria en donde los estudiantes informaron altos niveles de satisfacción respecto a un sistema flexible de aprendizaje de lenguas, considerando que podían trabajar a su propio ritmo y que tenían la oportunidad de realizar los trabajos de forma autónoma (Chateau y Zumbihl, 2012).…”
Section: Flexibilidad Vs Barreras De Tiempo En El Aprendizaje De Inglésunclassified
“…The system, first introduced in 2006, combines online work in a wirtual learning environment (VLE) that offers several types of resources and exercises, class sessions, collaborative work (in groups of two or three students), as well as counselling sessions, with counselling being understood here as it was defined by Gremmo (1995), among others. This learning system, already described in previous publications (e.g., Chateau & Zumbihl, 2010, 2012 has been gradually improved over the years, via students' feedback, and includes a number of guidance elements such as:…”
Section: Contextmentioning
confidence: 99%
“…This confirmed results found by Dam (2006) and Rivens and Eisenbeis (2009) that led these authors to conclude that students' logbooks helped them to become more autonomous. Furthermore, a later study (Chateau & Zumbihl, 2012) showed that students' comments in their logbooks illustrated "the necessary process of transformation that learners have to undergo in order to reach autonomy (Mozzon-McPherson, 2007;Portine, 1998) and [demonstrated that] it is a long and difficult process that requires support" (p. 171). That second study confirmed previous results and also showed the necessity to study the transformation process in more detail.…”
Section: Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…This paper suggests combining an integrative CALL approach with non-formal education to overcome the restrictions of the ESP classroom in targeting learner control. On the one hand, integrative CALL approaches can provide opportunities for a sustainable development of learner autonomy in ESP, especially where flexible language learning systems are devised to counterbalance the constraints of the HE lecture-based model (Chateaua & Zumbihla, 2012) and the one-size-fits-all approach. On the other, the importance of non-formal education has been acknowledged by the Parliamentary Assembly of the Council of Europe as the need to reinforce formal educational systems which cannot respond alone to the rapid technological changes in society (Recommendation 1437(Recommendation , par.…”
Section: Introductionmentioning
confidence: 99%